Afterlives [large type] - Gurnah, Abdulrazak, 1948- (Random House Large Print, 2022)
When he was just a boy, Ilyas was stolen from his parents on the coast of East Africa by German colonial troops. After years away, fighting against his own people, he returns home to find his parents gone and his sister, Afiya, little more than a slave to another family. Hamza too returns home from the war, scarred in body and soul and with nothing but the clothes on his back - until he meets the beautiful, undaunted Afiya. As these young people live and work and fall in love, their fates knotted ever more tightly together, the shadow of a new war on another continent falls over them, threatening once again to carry them away.--